Meaning-making of female genital cutting: children’s perception and acquired knowledge of the ritual - Schultz JH; Lien IL (Dove Medical Press, 2013)
Jon-Håkon Schultz, Inger-Lise Lien Norwegian Center for Violence and Traumatic Stress Studies, Oslo, Norway Abstract: How do girls who have undergone female genital cutting understand the ritual? This study provides an analysis of the learning process and knowledge acquired in their meaning-making process. Eighteen participants were interviewed in qualitative indepth interviews. Women in Norway, mostly with Somali or Gambian backgrounds, were asked about their experiences of circumcision. Two different strategies were used to prepare girls for circumcision, ie, one involving giving some information and the other keeping the ritual a secret. Findings indicate that these two approaches affected the girls' meaning-making differently, but both strategies seemed to lead to the same educational outcome. The learning process is carefully monitored and regulated but is brought to a halt, stopping short of critical reflexive thinking. The knowledge tends to be deeply internalized, embodied, and morally embraced. The meaning-making process is discussed by analyzing the use of metaphors and narratives. Given that the educational outcome is characterized by limited knowledge without critical reflection, behavior change programs to end female genital cutting should identify and implement educational stimuli that are likely to promote critical reflexive thinking. Keywords: female genital cutting, metaphors, health education, immigrants